2014
DOI: 10.1080/13691058.2014.887779
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of privacy and the non-disclosure of same-sex behaviour by behaviourally-bisexual men in heterosexual relationships

Abstract: Little attention has been paid to why some behaviourally-bisexual men (i.e., men who have sex with both men and women) choose not to disclose their same-sex behaviour. Using Communication Privacy Management theory (Petronio 2002), we report on the ways these men conceptualise their same-sex behaviour as private and thus feel justified in not disclosing it to family, friends, and female partners. In-depth interviews were conducted with an ethnically diverse sample of 203 non-disclosing behaviourally-bisexual me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Toller and McBride (2013) found that privacy rules established by parents as they explained grief and loss to their children implies that grief communication may be thought of as private information; however, our study provides systematic, empirical support for that notion. Schrimshaw et al (2014) took up a similar task in their study of behaviorally bisexual men's nondisclosures of their sexuality to opposite-sex partners, suggesting that choosing to conceal that information was based in the men's perceptions of what constituted private information. Here, we argue that because the bereaved think of their grief experiences as being characterized by information they own, CPM theory can provide insight into communication surrounding the grief process.…”
Section: Rq1: Privacy Ownershipmentioning
confidence: 97%
“…Toller and McBride (2013) found that privacy rules established by parents as they explained grief and loss to their children implies that grief communication may be thought of as private information; however, our study provides systematic, empirical support for that notion. Schrimshaw et al (2014) took up a similar task in their study of behaviorally bisexual men's nondisclosures of their sexuality to opposite-sex partners, suggesting that choosing to conceal that information was based in the men's perceptions of what constituted private information. Here, we argue that because the bereaved think of their grief experiences as being characterized by information they own, CPM theory can provide insight into communication surrounding the grief process.…”
Section: Rq1: Privacy Ownershipmentioning
confidence: 97%
“…This is highly problematic as research has consistently documented that bisexual men (both self-identified and behaviorally-bisexual) are significantly less likely to disclose their sexual orientation than gay men (Balsam & Mohr, 2007; Herek, Norton, Allen, & Sims, 2010; Lewis, Derlega, Brown, Rose, & Henson, 2009; Stokes, Vanable, & McKirnan, 1997; Wheeler, Lauby, Liu, Van Sluytman, & Murrill, 2008). Several studies in fact have suggested that the majority of behaviorally-bisexual men do not disclose their sexual orientation to their female partners (Agyemang, Wallace, & Liebman, 2008; Benoit & Koken, 2012; Kalichman, Roffman, Picciano, & Bolan, 1998; Stokes, McKirnan, Doll, & Burzette, 1996; Weatherburn, Hickson, Reid, Davies, & Crosier, 1998), to their friends and family members (Kalichman et al, 1998; Schrimshaw, Siegel, Downing, & Parsons, 2013), or to anyone (Reback & Larkins, 2010; Schrimshaw, Downing, Cohn, & Siegel, 2014). Non-disclosure by behaviorally-bisexual men is also associated with poorer mental health (Schrimshaw et al, 2013), more internalized homophobia (Lewis et al, 2009; Schrimshaw et al, 2013), and a greater likelihood of unprotected vaginal sex (Stokes et al, 1996; Tieu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, consistent with the identity development perspective, some men have reported not disclosing because they do not identify as bisexual or are uncertain about their sexual identity (Baldwin et al, in press, McCormack, Wignall, & Anderson, 2015; Wheeler, 2006). Other studies have found that some behaviorally-bisexual men report they conceal their sexual orientation because they feel others have no right to know this personal information, even their female sexual partners if they consistently use condoms (Malebranche et al, 2010; Schrimshaw et al, 2014). Furthermore, some research has suggested that prevalence and reasons for non-disclosure vary by the person to whom the men may disclose (Baldwin et al, in press; Dodge, Jeffries, & Sandfort, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…American Atheists president Dave Silverman later adopted the term (Corbin, 2011), and the atheist activist Richard Dawkins began his Out Campaign (www.outcampaign.org), intended to encourage other atheists to come out as atheists. The idea of coming out with reference to atheism has since made its way into the academic literature (Cimino & Smith, 2007;Krueger, 2013;Saeed & Grant, 2004;Smith, 2011). In this study, coming out as an atheist refers to disclosing to family members one's lack of belief in a god.…”
Section: Coming Out As An Atheistmentioning
confidence: 99%